2022
DOI: 10.1186/s12872-022-02490-3
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel-induced neutropenia in an 80-year-old patient with chronic kidney disease who underwent percutaneous coronary intervention: a case report and literature review

Abstract: Background Clopidogrel is a widely-used antiplatelet and acts as an adenosine diphosphate receptor inhibitor. Neutropenia is a rare but serious adverse effect of clopidogrel. It is unknown whether this adverse effect has any association with impaired kidney function. Case presentation An 80-year-old male with chronic kidney disease was diagnosed with non-ST elevation myocardial infarction and underwent percutaneous coronary intervention. During hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several studies have reported clopidogrelinduced agranulocytosis. [1][2][3] Additionally, stem cell activity is elevated after cerebrovascular events. 4,5 Wu et al 2 proposed a possible mechanism for clopidogrelinduced agranulocytosis, suggesting a toxic reaction that impairs the growth of myeloid colonies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported clopidogrelinduced agranulocytosis. [1][2][3] Additionally, stem cell activity is elevated after cerebrovascular events. 4,5 Wu et al 2 proposed a possible mechanism for clopidogrelinduced agranulocytosis, suggesting a toxic reaction that impairs the growth of myeloid colonies.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we believe that agranulocytosis was believed to result from a complex interplay between (1) bone marrow hematopoietic toxicity and (2) allergic reactions. Several studies have reported clopidogrel‐induced agranulocytosis 1–3 . Additionally, stem cell activity is elevated after cerebrovascular events 4,5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation